Analisis Gaya Kepemimpinan Islami Dalam Upaya Peningkatan Kinerja Karyawan (Studi Kasus Pada Usaha Rempeyek Ilham Kota Jambi) - Auliya Ainur Rahmah; Lucky Enggrani Fitri; Ridhwan . (Program Studi Ekonomi Syariah, Fakultas Ekonomi dan Bisnis Islam, Universitas Al Hikmah Indonesia, 2024)
This research aims to analyze the application of Islamic leadership styles that can help improve employee performance at the Rempeyek Ilham business in Jambi City. This study uses a qualitative descriptive method with data collection techniques such as observation, interviews, and documentation. The results of this research show that the application of Islamic leadership style in the Rempeyek Ilham business in Jambi City falls into the democratic leadership type (group developer) that focuses on employees and provides effective guidance to its employees, and the leadership style applied is in accordance with Islamic principles such as justice, consultation, and freedom of thought. In addition, the implementation of Islamic leadership styles in this business is also in line with Islamic values such as siddiq (honesty), amanah (trustworthiness), tabligh (conveying), and fatanah (intelligence). The factors that shape the Islamic leadership style in this business include the leader's personality, understanding in religion, the social environment, and the leader's vision and mission. The impact generated by the leadership style on employee performance is marked by an increase in job satisfaction, loyalty, and employee productivity. The impact generated by leadership style on employee performance is marked by increased job satisfaction, loyalty, and productivity of employees. With this alignment, employee performance in this business has also improved, and it can be said that Ilham Rempeyek has effectively applied Islamic leadership style.